Using GRM and PECS for improving reading skills in students with autism spectrum disorder - Navarro Arana, Cristian Edgardo; Calderón Joya, Daniela Ivon; García López, Yarly Paola (Revija za elementarno izobraževanje, 2024)
This case study analyzed the impact of GRM and PECS on the reading skills of two children with ASD with severity I and II. A descriptive cross-sectional quantitative approach was used with a pre-experimental, pre-test, post-test, and single-group design. The PROLEC-R Battery was applied before and after using the aforementioned strategies to measure students’ reading ability. Results showed that although both participants improved in the initial and lexical reading processes, only the participant with severity I reached a medium reading level. It was concluded that the used methods were successful, but longer exposure to them will likely yield better outcomes.